IDENTIFIKASI FAKTOR USIA, JENIS KELAMIN DENGAN LUAS INFARK MIOKARD PADA PENYAKIT JANTUNG KORONER (PJK) DI RUANG ICCU RSD DR. SOEBANDI JEMBER - susilo*, Cipto (The Indonesian Journal of Health Science, 2015)
Coronary Heart Disease (CHD) is one of the many diseases that cause deathas well as a health issue for countries that have developed or are being developed.The World Health Organization (WHO) also have expressed the fact that CHD is amodern epidemic and can not be avoided by a factor of aging. The predispositionfactor of CHD include age and gender, with the incidence in men much more thanwomen but the incidence in women increases after menopause around the age of 50years due to the influence of the hormone estrogen has a protective effect on theoccurrence of atherosclerosis. Increasing age may also increase the incidence ofCHD, because the blood vessels undergo progressive change and continues over aperiod of time. This study aims to identify factors of age, gender with an area ofmyocardial infarction in CHD. This research is an observational description andsampling techniques with consecutive sampling. Results of analysis using cross tabulationshows the average area of myocardial infarction based on the scores selvesterbetween 11-20% and 21% -30% with each numbered 4 (20%) aged between 60-69years and gender male number 7 (35%) with an area of infarction of 11% -20%.The conclusion of this study that that the extensive occurrence of myocardialinfarction in men more spacious when compared to women, whereas in age mostlyoccurs at age 50-69 years.